Verbal Antithesis in the Holy Quran: A Rhetorical, Statistical and Analytical Study - Al-Farsi, Ahmed Mohammed (Journal of Arabic Language Sciences and Literature, 2025)
The current study aims to analyze the verbal antithesis in the Holy Quran; in order to understand its rhetorical and semantic dimensions. The study relied on the analytical statistical method, to monitor and classify the verses. The study analyzed the Quranic verses that contain verbal antithesis and classified the antithesis into positive and negative antithesis. The study recommends using its results as a reference for additional linguistic and rhetorical studies. The research started in involved and analyzed numbers of versus from the Holy Quran and began to clarify different types and kinds of eloquence from these versus. Where the second parts focused on the metaphor counterfactual. Then ended the chapter with a table contains some examples of metaphoric from the versus of the Holy Quran. At the end, the research concluded his research with the eloquence results which he come out from his research. this was clear evidence of the strong structures of the Holy Quran where connected words and sentences showed clearly.